Reception of Students of SMA Negeri 5 Sarolangun for The Silent Piece (1949) Music Composition by John Cage - Muhammad Egi; Nusyirwan Nusyirwan; Selvi Kasman; Rosmegawaty Tindaon (Universitas Negeri Medan, 2023)
Broadly speaking, we can associate music with sound. The association received a